Tracking the fungus‐assisted biocorrosion of lead metal by Raman imaging and scanning electron microscopy technique. (21st January 2020) - Wu, Yiling; Shao, Xiaoqing; Jiao, Hang; Song, Xinwei; He, Kun; Li, Zhen
Abstract: Fungi play a significant role in biological corrosion of metal materials. We studied the biocorrosion of lead foils under incubation of Aspergillus niger ( A . niger ). Multiple techniques, for example, scanning electron microscopy (SEM), diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), and Raman imaging and scanning electron microscopy (RISE), were applied in this study. SEM confirmed the normal growth of the fungus on Pb foil surface, either above or under the solid medium surface. In addition, SEM‐energy dispersive spectrometer confirmed the formation of the secondary Pb mineral particles after incubation, which had variable morphologies. DRIFT was able to show changes of compounds formed on the surface of Pb foils. However, it cannot exactly identify the mineral phase. RISE technology offered both morphological and spectral information of the formed Pb mineral. Three dominant Raman peaks at ~1, 440, ~1, 480, and ~1, 590 cm −1 indicated that the secondary mineral was lead oxalate. Raman mapping further demonstrated the distribution of Pb oxalate architecture. This study first applied RISE to investigate the biocorrosion of metals by fungi. Abstract : We studied the biocorrosion of lead foils under incubation of Aspergillus niger. Multiple techniques, for example, scanning electron microscopy (SEM), diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), and Raman imaging and scanning electron microscopy (RISE), were applied in this study. RISE technology offered both morphological and spectral information of the formed Pb‐mineral. Three dominant Raman peaks indicated that the secondary mineral was lead oxalate. Raman mapping further demonstrated the distribution of Pb oxalate architecture. This study first applied RISE to investigate the biocorrosion of metals by fungi.